1982
DOI: 10.1172/jci110620
|View full text |Cite
|
Sign up to set email alerts
|

Role of Propranolol in Improvement of the Relationship between O2 Supply and Consumption in an Ischemic Region of the Dog Heart

Abstract: A B S T R A C T Several aspects of the myocardial 02 supply/consumption relationship were determined after coronary artery occlusion and subsequent /l-adrenergic blockade in 16 anesthetized open-chest dogs. Small artery and vein 02 saturations, and hence extraction, were obtained microspectrophotometrically and combined with radioactive microsphere blood flow determinations to calculate regional myocardial 02 consumption. Eight dogs remained untreated after coronary artery ligation while another group was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This mechanism may also be important with complement depletion as decreased microvascular obstruction may decrease microregional flow heterogeneity. As performed previously, changes in flow distribution may be estimated by measuring changes in microregional SvO2 distribution as measured by microspectrophotometry (4). In the present study no changes in SvO 2 distribution were observed though this does not totally eliminate the possibility of an altered flow distribution within the ischemic zone.…”
Section: Basic Research Insupporting
confidence: 51%
See 1 more Smart Citation
“…This mechanism may also be important with complement depletion as decreased microvascular obstruction may decrease microregional flow heterogeneity. As performed previously, changes in flow distribution may be estimated by measuring changes in microregional SvO2 distribution as measured by microspectrophotometry (4). In the present study no changes in SvO 2 distribution were observed though this does not totally eliminate the possibility of an altered flow distribution within the ischemic zone.…”
Section: Basic Research Insupporting
confidence: 51%
“…Previous studies from our laboratory have shown that a decreased microregional heterogeneity of flow to an ischemic region can be associated with a decreased severity of ischemia, even when the total ischemic regional flow is constant (4). This mechanism may also be important with complement depletion as decreased microvascular obstruction may decrease microregional flow heterogeneity.…”
Section: Basic Research Inmentioning
confidence: 80%
“…The extensive collateral network in the rabbit heart was determined by Weiss (1982), where LAD occlusion decreased coronary blood flow by approximately 50%, as was observed also in the present study. This is in contrast to the 70-75% reductions in blood flow in the dog occlusion model (Gorman & Sparks 1980;Conway & Weiss 1982). Rabbits also have a high degree of noncollateral overlap flow, comprising approximately 21% of the blood flow to an occluded region (Weiss 1982).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it has been suggested that when myocardial oxygen consumption of the ischemic myocardium is reduced by /3-adrenergic blockade (slowed heart rate and reduced arterial pressure), the discrepancy between the demand for blood flow and the limited supply to the ischemic tissue is attenuated, which may result in improved regional function. 9 Finally, reduced left ventricular pressure (LVP) during exercise following /3-blockade 1 may contribute to the improvement in regional myocardial function in the ischemic myocardium. Thus, a variety of mechanisms potentially have a role in reducing exercise-induced regional myocardial ischemia and dysfunction.…”
mentioning
confidence: 99%